CV. Lifestone’s Employee Work Commitment: Reviewed in Terms of Compensation, Work Environment, and Task Complexity - Riska Rahmawati; Vera Firdaus; Dewi Andriani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to investigate the relationship and impact of compensation, work environment, and task complexity on the level of commitment shown by employees at CV. Lifestone. The type of research conducted by the author in this study is descriptive quantitative research, which collects data from 90 respondents. The research location chosen by the author to test the hypothesis is at the CV. Lifestone office located at Permata Gedangan Warehouse Complex, Block AF No. 1, Bohar, Gedangan District. Data were analyzed using SmartPLS 5.0 software, including Outer Model Test Analysis, Validity Test, Reliability Test, Average Variance Extracted (AVE) Test, R-square Test, and Hypothesis Test. The results show that compensation positively affects employee work commitment (T=6.831, p=0.000), work environment positively affects employee work commitment (T=4.849, p=0.000), and task complexity also positively affects employee work commitment (T=5.662, p=0.000). This study found that the three independent variables (compensation, work environment, and task complexity) simultaneously had a positive and significant effect on work commitment, indicating that fair compensation, a supportive work environment (especially job security), and a challenging and coordinated level of task complexity effectively increase employee dedication and responsibility towards the company.